Replication of the R6K plasmid during the Escherichia coli cell cycle. - Keasling, J D (1992)
The cell-cycle replication pattern of the R6K plasmid has been investigated by using the membrane-elution technique to produce cells labelled at different times during the division cycle and scintillation counting for quantitative analysis of radioactive plasmid DNA. The high-copy plasmid R6K replicates exponentially in a cell-cycle-independent manner. A mini-R6K plasmid deleted for the ori alpha origin of replication also replicates, exponentially in a cell-cycle-independent manner.